Studies on Furosemide Salicylaldehyde Schiff Base Complex with Copper(II) and Zinc(II) - Bhattacharya, Mamta; Malik, Suman; Iqbal, S.A. (Asian Journal of Chemistry, 2010)
The synthesis and characterization of metal complexes of Zn(II) and Cu(II) using Schiff base ligand salicylaldehyde furosemide is reported. Furosemide is a diuretic drug and it is used to increase the rate of urination through kidneys. Analytical data and stoichiometry suggest ligand-metal ratio as 2 : 1. The structure assigned to the complexes, synthesized via Schiff base formation is supported by infrared spectral studies.